Generalized maximal functions and related operators on weighted Musielak-Orlicz spaces - Bernardis, Ana Lucia (2014)
We characterize the class of weights related to the boundedness of maximal operators associated to a Young function η in the context of variable Lebesgue spaces. Fractional versions of these results are also obtained by means of a weighted Hedberg type inequality. These results are new even in the classical Lebesgue spaces. We also deal with Wiener’s type inequalities for the mentioned operators in the variable context. As applications of the strong type results for the maximal operators, we derive weighted boundedness properties for a large class of operators controlled by them.